Hubungan Pengetahuan Ibu Terhadap Proses Penyembuhan Luka Perineum Pada Ibu Nifas di Wilayah Pedesaan Percut, Sumatera Utara - Netti Meilani Simanjuntak; Dian Andriyani Syafitri (STIKes Karsa Husada Garut, 2020)
Maternal mortality in Asia is still very high, several factors influence such as a dense population, poverty, lack of maternal and child health services, and most importantly is maternal knowledge. The purpose of this study is to identify the relationship between the level of maternal knowledge about perineum wound care and the wound healing process in postpartum mothers in rural areas. The research method was cross sectional, with a total sampling, 30 postpartum mothers were joined in this study. The results showed there was a significant relationship between the level of maternal knowledge with the process of wound healing in postpartum mothers (p value = 0.008). Therefore health services such as independent practice midwives must have programs to improve postpartum maternal knowledge after parturition. So that it helps the mother in the process of healing the wound and there is no infection.